Assessment of the educational value of undescended testicle operation videos on YouTube (Annals of Medical Research, 2024)
Aim: Today, Youtube, which is also used as a source of health information, is one of the most visited social platforms. The aim of this study was to evaluate the content and reliability of videos on undescended testicular operations for surgeons and parents.Materials and Methods: On 25/9/2023, the keywords "undescended testicle operation," "orchiopexy," and "children" were searched on the YouTube search engine. The selected videos were divided into two groups: useful and misleading. In addition to the descriptive characteristics of the videos, the reliability, quality and content of the videos were analysed using the global quality score (GQS), modified DISCERN (mDISCERN), and video power index (VPI) score.Results: Of the 62 videos evaluated in our study, 69.4% (n=43) were of high quality, 14.5% (n=9) were of medium quality and 16.1% (n=4) were of low quality. GQS and mDISCERN scores were higher in the useful group (p=0.002, p=0.001, respectively). While 91.1% (n=51) of the videos in the useful group were addressed to healthcare professionals (p=0.024), 78.6% (n=44) of these videos were uploaded by physicians. A positive correlation was observed between GQS and mDISCERN scores (p
Keywords: YouTube; Undescended testis operation; Orchiopexy; Children